MODELING OF TECHNICAL SYSTEM IN THE ENVIRONMENT OF PROGRAM COMPLEX “МВТУ” - B.A. KARTASCHOV; O.S. KOZLOV; I.K. VINNIKOV; S.N. LITVINOV (Advanced Engineering Research)
Data on a domestic program complex «МВТУ» are short stated. The example of modeling of the technical system, illustrating high efficiency of a program complex is resulted.